MicroRNA control of B cell tolerance, autoimmunity and cancer. (August 2020) - Xiao, Changchun; Nemazee, David; Gonzalez-Martin, Alicia
Abstract: Since the discovery of the first microRNA (miRNA) in 1993, thousands of miRNAs have been identified in humans and mice and many of them have been shown to control a large variety of cellular processes in different cell types including those composing the immune system. MicroRNAs regulate virtually all aspects of immune cell development, differentiation and function. Studies have shown that these molecules are involved in the maintenance of lymphocyte tolerance and, when dysregulated, promote the development of autoimmune diseases. In this review, we focus on the current knowledge about the roles of miRNAs in B cell tolerance and their contribution to autoimmunity, highlighting additional roles for some of these miRNAs in T cell tolerance. Finally, we will comment on miRNAs that promote both autoimmunity and lymphoma.